The hierarchical structure of error-related negativities elicited from affective and social stimuli and their relations to personality traits. (5th January 2020) - Suzuki, T.; Novak, K. D.; Ait Oumeziane, B.; Foti, D.; Samuel, D. B.
Abstract: Psychophysiological measures have become increasingly accessible to researchers and many have properties that indicate their use as individual difference indicators. For example, the error-related negativity (ERN), an event-related potential (ERP) thought to reflect error-monitoring processes, has been related to individual differences, such as Neuroticism and Conscientiousness traits. Although various tasks have been used to elicit the ERN, only a few studies have investigated its variability across tasks when examining the relations between the ERN and personality traits. In this project, we examined the relations of the ERN elicited from four variants of the Flanker task (Arrow, Social, Unpleasant, and Pleasant) that were created to maximize the differences in their relevance to personality traits. A sample of 93 participants with a history of treatment for psychopathology completed the four tasks as well as self-report measures of the general and maladaptive five-factor model (FFM) traits. Confirmatory factor analyses (CFAs) of ERN amplitudes indicated that three of the four tasks (Arrow, Social, and Unpleasant) were unidimensional. Another set of CFAs indicated that a general factor underlies the ERN elicited from all tasks as well as unique task-specific variances. The correlations of estimated latent ERN scores and personality traits did not reflect the hypothesized correlation patterns. Variability across tasks and the hierarchical model of the ERN may aid in understanding psychopathology dimensions and in informing future endeavors integrating the psychophysiological methods into the study of personality. Recommendations for future research on psychophysiological indicators as individual differences are discussed.